2022
DOI: 10.1186/s12263-021-00703-6
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in patients with obesity and metabolic disorders — a systematic review

Abstract: Background Previous observational studies have demonstrated inconsistent and inconclusive results of changes in the intestinal microbiota in patients with obesity and metabolic disorders. We performed a systematic review to explore evidence for this association across different geography and populations. Methods We performed a systematic search of MEDLINE (OvidSP) and Embase (OvidSP) of articles published from Sept 1, 2010, to July 10, 2021, for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 104 publications
(181 reference statements)
4
68
2
4
Order By: Relevance
“…This study analyzed the gut microbiota of 204 twins from 129 families at three age stages and demonstrated that five gut microbiota, genera Akkermansia, Parabacteroides, Clostridium innocuum group, Roseburia , and Anaerostipes , were correlated with BMI_Z. As short-chain fatty acid producers, Akkermansia, Roseburia , and Anaerostipes were previously reported to be associated with obesity in animal models and adults ( Pinart et al, 2021 ; Gao et al, 2022 ; Pai et al, 2022 ; Xu et al, 2022 ; Zou et al, 2022 ). There were only two studies that reported a positive association between Akkermansia and BMI_Z in early childhood in singleton children, which was consistent with our findings ( Houtman et al, 2022 ; Reyna et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…This study analyzed the gut microbiota of 204 twins from 129 families at three age stages and demonstrated that five gut microbiota, genera Akkermansia, Parabacteroides, Clostridium innocuum group, Roseburia , and Anaerostipes , were correlated with BMI_Z. As short-chain fatty acid producers, Akkermansia, Roseburia , and Anaerostipes were previously reported to be associated with obesity in animal models and adults ( Pinart et al, 2021 ; Gao et al, 2022 ; Pai et al, 2022 ; Xu et al, 2022 ; Zou et al, 2022 ). There were only two studies that reported a positive association between Akkermansia and BMI_Z in early childhood in singleton children, which was consistent with our findings ( Houtman et al, 2022 ; Reyna et al, 2022 ).…”
Section: Discussionmentioning
confidence: 97%
“…Yoshida et al reported that oral administration of Bacteroides in mice prone to atherosclerosis reduced lipopolysaccharide production by intestinal microorganisms and suppressed the formation of atherosclerotic lesions (Yoshida et al, 2018). The genus Bacteroides is also abundant in the intestines of healthy adults (The human microbiome project consortium, 2012 ), and many studies have reported that they have anti-obesity effect (Xu et al, 2022). Yoshida et al (Yoshida et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The most recent studies comparing the gut microbiome in adults with obesity and control groups have demonstrated that gut microbiota diversity in obese people is significantly decreased, and there are significant differences between the microbiota of these two groups at different levels, from phylum to species. Furthermore, it has been shown that obese people have abnormalities mainly with respect to carbohydrate and lipid metabolism pathways compared to the control group [ 68 , 69 , 70 , 71 ]. Additionally, comparing the structure of the gut microbiota between obese and normal school-age children revealed that the gut microbiota in obese children was less diverse than in the control group.…”
Section: The Interplay Of the Gut Microbiota Inflammation And Obesitymentioning
confidence: 99%